Degradasi Moral Dalam Pendidikan Karakter Islam Peserta Didik Akibat Dari Penggunaan Gadget Tanpa Pengawasan Intensif - Siti Nur Kholifah; Sistya Pratiwi; Chanifudin Chanifudin (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This article aims to describe the problems of Islamic education relating to students and educators, as well as efforts to deal with them. Problems that challenge the implementation of Islamic education include moral degradation in students' Islamic character education as a result of the use of gadgets without intensive supervision, where efforts to address these educational problems require cooperation between students' parents and teachers to supervise students' use of gadgets. who are currently using it, where with more intensive supervision it is hoped that it can minimize the negative impact of the use of gadgets by students, especially on moral degradation in Islamic character education.